Chitosan-based liposomal thermogels for the controlled delivery of pingyangmycin: design, optimization and in vitro and in vivo studies - Ling Zhang; Fen Chen; Jiatong Zheng; Hongwei Wang; Xingjun Qin; Weisan Pan (Taylor & Francis Group, 2018)
Pingyangmycin (PYM) has been applied clinically for many years to treat vascular malformations (VM) in China. The major limitation of PYM injections is quick diffusion from the injection site, which increases side effects, especially the possibility of pulmonary injury. In this paper, chitosan/glycerophosphate disodium (CS/GP) thermogels containing liposomes for sustained and localized PYM delivery were prepared and optimized by a three-level three-factorial Box-Behnken experimental design to evaluate the effects of different variables (the PYM concentration, CS amount and GP content), on the selected responses (cumulative percentage PYM released in 1 day, 9 days and the rate constant k). The results revealed that the optimized PYM liposomal thermogels had a controlled PYM release for 14 days in vitro, which confirmed the validity of optimization. In vitro morphological observation, cell cycle and apoptosis analysis showed an effective anti-proliferation action of PYM liposomal thermogels on human vascular endothelial cells (EA.hy926). In vivo pharmacokinetics research in rabbits displayed that compared with PYM liposomes and PYM thermogels, PYM liposomal thermogels had a better controlled delivery of PYM. Histological examination of rabbit ear veins showed that after local application with PYM lipsomal thermogels for 21 days, obvious vein thrombosis and inflammatory reaction could be observed. The above results indicated that PYM-loaded lipsomal CS/GP thermogels might have a good prospect for the treatment of VM.